ENROLLMENT COMPETITION, ADMISSION AND GRADUATION: REGULARITY OF INTERCONNECTION - Victoria F. Pugach (Высшее образование в России)
The article reveals research results of social trends in students’ migration of RSFSR/Russian HEIs in 1959-1999 including the analysis from the point of view HEIs’ branch affiliation. Educational statistics enables to review the stability parameters for student groups (share of graduates from the number of enrolled) plus correlation between the indexesof stability and enrollment competition. Examination of interconnection between rank consequence of HEI’s branch affiliation on stability and competition (with the help of Spearmen rank correlation coefficients) gave the following regularity: the harder the HEI enrollment competition the more stable are student groups and the lower the number of screened out.